Trends in mortality from aortic dissection analyzed from the World Health Organization Mortality Database from 2000 to 2017. (1st August 2022) - Abdallah, N.; Mouchati, C.; Crowley, C.; Hanna, L.; Goodall, R.; Salciccioli, J.D.; Marshall, D.C.; Gibbs, R.G.J.; Shalhoub, J.
Abstract: Background: We assessed trends in aortic dissection (AD) death rates in 23 countries from 2000 to 2017. Methods: We extracted AD mortality data for countries with high usability data from the World Health Organization (WHO) Mortality Database and from the Center for Disease Control (CDC) WONDER Database for the United States of America (USA). Age Standardized Death Rates (ASDRs) per 100, 000 population were computed. Trends were assessed by locally weighted scatter plot smoother (LOWESS) regression. Results: Between 2000 and 2017, ASDRs from AD decreased in Australia, Belgium, Croatia, Denmark, France, Italy, New Zealand, Norway, Sweden, the United Kingdom, and the USA for both sexes. Increasing AD mortality was observed in Austria, Czech Republic, Germany, Hungary, Israel, and Japan for both sexes. The largest absolute increases in ASDR were in Japan for men (+1.59) and women (+ 1.11). The largest percentage decreases were in Norway for men (−0.91) and in New Zealand (−0.6) for women. In 2017, the highest mortality rates were in Japan for both sexes (3.22 and 2.09, respectively). The lowest ASDR was in Kyrgyzstan for both sexes (0.16 and 0.10, respectively). ASDRs for AD in 2017 were higher for men than women in all countries included. Spain had the greatest difference between the gender's mortality rates with a 2.71-fold higher mortality average rate in men. Conclusion: We identified an overall decrease in AD mortality in most included countries, while an increase was noted in other countries including Israel and Japan. Highlights: In 2000-2017, mortality from aortic dissection decreased in Australia, the USA, and many European countries. Increasing mortality was seen in Austria, the Czech Republic, Germany, Hungary, Israel, with the largest increase in Japan. In 2017, the highest mortality rates were in Japan and the lowest in Kyrgyzstan. The age-standardized death rates in 2017 were higher for men than women.